How many people in the Netherlands live with a hip, knee, or shoulder replacement?: prevalence estimates using data from the Dutch Arthroplasty Register (LROI) and Statistics Netherlands - Mirthe H. W. van Veghel; Liza N. van Steenbergen; Maaike G. J. Gademan; Wilbert B. van den Hout; B. W. Schreurs; Gerjon Hannink (Bone & Joint Open)
Aims: We estimated the prevalence of people living with at least one hip, knee, or shoulder arthroplasty in the Netherlands. Methods: We included the first hip (n = 416,333), knee (n = 314,569), or shoulder (n = 23,751) arthroplasty of each patient aged ≥ 40 years between 2007 and 2022 (hip/knee) or 2014 and 2022 (shoulder) from the Dutch Arthroplasty Register (LROI). Data on the size of the Dutch population were obtained from Statistics Netherlands. Annual incidences and deaths from hip and knee arthroplasty since 2010, and shoulder arthroplasty since 2015, were observed from the LROI. Annual incidences and deaths before those years were estimated using Poisson regression analyses and parametric survival models based on a Gompertz distribution. Non-parametric percentile bootstrapping with resampling was used to estimate 95% CIs. Results: Annual incidences per 100,000 Dutch inhabitants aged ≥ 40 years increased for hip arthroplasties from 221 (95% CI 214 to 229) in 1990 to 360 in 2022, for knee arthroplasties from 181 (95% CI 174 to 188) to 272, and for shoulder arthroplasties from 11 (95% CI 8.0 to 16) to 34. In 2022, 791,000 (95% CI 787,000 to 794,000) people in the Netherlands were living with at least one joint replacement, representing 8.4% (95% CI 8.4 to 8.5) of the Dutch population aged ≥ 40 years. For hip, knee, and shoulder arthroplasties, these were 436,000 (95% CI 433,000 to 438,000), 383,000 (95% CI 380,000 to 386,000), and 34,000 (95% CI 33,000 to 36,000) people, corresponding to 4.7% (95% CI 4.6 to 4.7), 4.1% (95% CI 4.1 to 4.1), and 0.4% (95% CI 0.3 to 0.4) of the Dutch population, respectively. The most common age group living with at least one joint replacement was the ≥ 80-year age group, representing 38% (95% CI 37 to 38) of the Dutch population aged ≥ 80 years. Conclusion: Approximately 800,000 people in the Netherlands were living with at least one hip, knee, or shoulder replacement in 2022, representing one in 12 Dutch inhabitants aged ≥ 40 years. Cite this article: Bone Jt Open 2025;6(1):74–81.